Factors Affection Entrepreneurship Development in Surkhet District (The Gaze: Journal of Tourism and Hospitality, 2024)
Entrepreneurship, an ancient and transformative phenomenon, ispivotal for societal and economic development. It involvesidentifying innovative ideas and establishing new enterprises,distinguishing itself from self-employment, which lacksentrepreneurial risk-taking, resource mobilization, and productionorganization. Entrepreneurs significantly contribute to nationalincome and rural prosperity through their ventures. This studyemploys a mixed-method approach, integrating correlational andcausal-comparative research designs to explore factorsinfluencing entrepreneurship development in Surkhet district,Nepal. Data were collected via structured questionnaires with afive-point Likert scale using purposive sampling. Quantitative datawere analyzed using SPSS, employing descriptive statistics,correlation and regression analyses, factor analysis, Cronbach’salpha, and multicollinearity tests. The findings confirm significantrelationships between entrepreneurship development andvariables such as training, government policies, environmentalfactors, NGO support, and raw materials availability. Theseresults emphasize the importance of multifaceted support systemsfor fostering entrepreneurship. Future research is encouraged toexplore dynamic policy analysis, policy interactions, and theevolving ecosystem of entrepreneurial development.